Drug Release Studies from Caesalpinia pulcherrima Seed Polysaccharide - Jeevanandham, Somasundaram (Shaheed Beheshti University of Medical Sciences, 2011)
This study examines the controlled release behavior of both water-soluble (acetaminophen, caffeine, theophylline and salicylic acid) and water insoluble (indomethacin) drugs derived from Caesalpinia pulcherrima seed Gum isolated from Caesalpinia pulcherrima kernel powder. It further investigates the effect of incorporating diluents such as microcrystalline cellulose and lactose on caffeine release. In addition the effect the gum’s (polysaccharide) partial cross-linking had on release of acetaminophen was examined. Applying the exponential equation, the soluble drugs mechanism of release was found to be anomalous. The insoluble drugs showed a near case II or zero order release mechanism. The rate of release in descending order was caffeine, acetaminophen, theophylline, salicylic acid and indomethacin. An increase in the release kinetics of the drug was observed on blending with diluents. However, the rate of release varied with the type and amount of blend within the matrix. The mechanism of release due to effect of diluents was found to be anomalous. The rate of drug release decreased upon partial cross-linking and the mechanism of release was found to be of super case II.